An international registry for primary ciliary dyskinesia. Issue 3 (9th December 2015) - Werner, Claudius; Lablans, Martin; Ataian, Maximilian; Raidt, Johanna; Wallmeier, Julia; Große-Onnebrink, Jörg; Kuehni, Claudia E.; Haarman, Eric G.; Leigh, Margaret W.; Quittner, Alexandra L.; Lucas, Jane S.; Hogg, Claire; et al.
Primary ciliary dyskinesia (PCD) is a rare autosomal recessive disorder leading to chronic upper and lower airway disease. Fundamental data on epidemiology, clinical presentation, course and treatment strategies are lacking in PCD. We have established an international PCD registry to realise an unmet need for an international platform to systematically collect data on incidence, clinical presentation, treatment and disease course. The registry was launched in January 2014. We used internet technology to ensure easy online access using a web browser underwww.pcdregistry.eu . Data from 201 patients have been collected so far. The database is comprised of a basic data form including demographic and diagnostic information, and visit forms designed to monitor the disease course. To establish a definite PCD diagnosis, we used strict diagnostic criteria, which required two to three diagnostic methods in addition to classical clinical symptoms. Preliminary analysis of lung function data demonstrated a mean annual decline of percentage predicted forced expiratory volume in 1 s of 0.59% (95% CI 0.98–0.22). Here, we present the development of an international PCD registry as a new promising tool to advance the understanding of this rare disorder, to recruit candidates for research studies and ultimately to improve PCD care. A registry to systematically collect data on clinical presentation, disease course and treatment of PCD http://ow.ly/TtGAR